Occurrence of human-associated Bacteroidetes genetic source tracking markers in raw and treated wastewater of municipal and domestic origin and comparison to standard and alternative indicators of faecal pollution. (1st March 2016) - Mayer, R.E.; Bofill-Mas, S.; Egle, L.; Reischer, G.H.; Schade, M.; Fernandez-Cassi, X.; Fuchs, W.; Mach, R.L.; Lindner, G.; Kirschner, A.; Gaisbauer, M.; Piringer, H.; et al.
Abstract: This was a detailed investigation of the seasonal occurrence, dynamics, removal and resistance of human-associated genetic Bacteroidetes faecal markers (GeBaM) compared with ISO-based standard faecal indicator bacteria (SFIB), human-specific viral faecal markers and one human-associated Bacteroidetes phage in raw and treated wastewater of municipal and domestic origin. Characteristics of the selected activated sludge wastewater treatment plants (WWTPs) from Austria and Germany were studied in detail (WWTPs, n = 13, connected populations from 3 to 49000 individuals), supported by volume-proportional automated 24-h sampling and chemical water quality analysis. GeBaM were consistently detected in high concentrations in raw (median log10 8.6 marker equivalents (ME) 100 ml −1 ) and biologically treated wastewater samples (median log10 6.2–6.5 ME 100 ml −1 ), irrespective of plant size, type and time of the season (n = 53–65). GeBaM, Escherichia coli, and enterococci concentrations revealed the same range of statistical variability for raw (multiplicative standard deviations s* = 2.3–3.0) and treated wastewater (s* = 3.7–4.5), with increased variability after treatment. Clostridium perfringens spores revealed the lowest variability for raw wastewater (s* = 1.5). In raw wastewater correlations among microbiological parameters were only detectable between GeBaM, C. perfringens and JC polyomaviruses. Statistical associations amongst microbial parameters increased during wastewater treatment. Two plants with advanced treatment were also investigated, revealing a minimum log10 5.0 (10th percentile) reduction of GeBaM in the activated sludge membrane bioreactor, but no reduction of the genetic markers during UV irradiation (254 nm). This study highlights the potential of human-associated GeBaM to complement wastewater impact monitoring based on the determination of SFIB. In addition, human-specific JC polyomaviruses and adenoviruses seem to be a valuable support if highly specific markers are needed. Graphical abstract: Highlights: Dynamics of human-associated Bacteroidetes in raw and treated wastewater is presented. High concentrations of Bacteroidetes occur irrespective of plant size, type, season. We compared bacterial, viral and process parameters due to wastewater treatment. Human-associated GeBaM were found valuable to monitor wastewater impact. Human-specific JC polyomaviruses and adenoviruses are highly specific markers.